Yurisdiksi Penegakan Hukum Tindak Pidana Cybercrime di Indonesia Pasca Reformasi - Devi Vanessa Armi Putri; Khanza Aoera Dievana (Jurnal Hukum dan Sosial Politik, 2024)
The purpose of this article is to examine the criminal hoax law in Indonesia and the gaps in the state’s efforts to combat criminal hoaxes. Hoax news refers and points to a situation that is currently being discussed, the more people are triggered, the more aggressively the news is spread. In order to overcome the problem of cybercrime that is growing rapidly in Indonesia, the government made a legislation that specifically regulates cyberlaw which is realized in Law Number 11 of 2008 concerning Electronic Information and Transactions Law. “Law No. 11 of 2008” is one of the efforts to overcome cybercrime juridically and emperically, even though “ Law No. 11 of 2008” does not only discuss the issue of obscene or pornographic sites, buat also regulates the rules of electronic transactions which are the legal umbrella in cyberlaw rules in Indonesia. The conclusion of this research is thatm normatively, hoaxes are different from criticism and the restrictions on hoaxes in the Criminal Code and ITE Law are explicit. Since criticism is an important component of democratic life, ending democracy also means ending the practice of criticsm. The political aspects that control the structure of the Indonesian state make it difficult for the law to operate in an orderly fashion, which presents challenges for law enforcement agencies trying to combat the crime of hoaxes.